Steel for offshore wind turbines of class 36 kg with high modulus of elasticity and method for its production
Patent Information
- Application Number
- CN202611375352.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
[0016]1、目前已公开的高弹性模量钢技术方案多采用高合金元素、金属间化合物及复杂粉末冶金工艺,增加了材料的制造成本,难以适应海上风电装备大批量生产需求
[0056](1)本发明通过采用低C、Mn+Cr-Cu耐海水飞溅腐蚀合金化+Ti-B原位析出增强相+Nb微合金化的成分设计,在低C、低Mn体系保证高铁素体比例和良好的塑性储备基础上,添加Cr、Cu以形成稳定、均匀的耐蚀锈层,并通过Nb微合金化细化组织。
Smart Images

Figure CN122879616A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medium and thick steel plates, and particularly relates to a 36kg grade structural steel for offshore wind power with high elastic modulus and seawater splash corrosion resistance, and its manufacturing method. Background Technology
[0002] As an emerging industry for achieving green energy transformation and high-quality development, offshore wind power is rapidly expanding its installed capacity and application scenarios to deep and remote seas. Compared to onshore wind power, offshore wind power equipment faces more complex natural environments and more stringent structural safety challenges during service, including the combined effects of strong wind loads, wave impacts, hydrodynamic interference, sea ice loads, tidal forces, and long-term corrosion from multiple sources. These external environmental conditions require wind turbine structures to possess higher stiffness control capabilities, deformation stability, and operational reliability throughout their entire lifecycle. With the continuous increase in the power of offshore wind turbines and the expansion of their overall size, the total tower height of megawatt-class wind turbines often exceeds 140 meters, the hub center height continues to rise, and the rotor diameter even exceeds 120 meters. This massive structural system needs to maintain overall coordinated deformation and local vibration resistance under multi-axis coupled loads to avoid structural instability such as resonance, instability, or stress concentration failure. This complex dynamic behavior places higher demands on the stiffness properties of materials, especially the elastic modulus.
[0003] The elastic modulus is a fundamental parameter that measures a material's ability to undergo elastic deformation under unit stress, directly determining the stiffness level and first-order natural frequency of structural components. In critical structures such as wind turbine towers, jacket structures, and pile foundations, increasing the material's elastic modulus not only helps control overall deformation but also effectively raises the structure's natural frequency, reducing the risk of resonance between wind-induced and wave-induced excitation and the structure's natural modes. This reduces fatigue accumulation effects and vibration amplitude, extending service life. Furthermore, high-elastic-modulus steel can also offer significant cost-saving and efficiency-enhancing potential by reducing structural wall thickness or increasing stiffness per unit mass. However, the elastic modulus is an intrinsic property of a material, primarily determined by interatomic bonding forces and crystal structure. Traditional alloy composition design, rolling, or heat treatment processes cannot significantly alter this intrinsic property of steel. Therefore, the difficulty in achieving stiffness enhancement with traditional wind power steel has become one of the core factors restricting the optimization of wind power equipment structural design.
[0004] While structural steels widely used in current engineering practice meet basic structural requirements in terms of strength and toughness—for example, existing DH36, EH36, and similar structural steels mainly achieve a balance between strength and toughness through C-Mn low alloying and controlled rolling and cooling—their elastic modulus is typically in the range of 200–210 GPa. For medium-thick steel plates used in the lower section of towers and the upper part of jacket structures, simply increasing strength cannot simultaneously solve the problem of insufficient stiffness; if stiffness is compensated by increasing wall thickness, it will increase self-weight, welding workload, and transportation and installation burdens.
[0005] Currently, relevant domestic and international standards such as GB / T 1591 "Low-alloy High-strength Structural Steel", GB / T 712 "Structural Steel for Ships and Marine Engineering", EN10025, and EN10225 have provided general strength grades of steel foundations for wind power structures. However, a systematic design and material matching system has not yet been formed for stiffness performance indicators. The lack of systematic optimization and clear constraints on the elastic modulus parameter in existing material systems limits further improvements in high-order dynamic response control, overall stiffness enhancement, and stability under ultimate loads for wind power structures.
[0006] In summary, developing a series of wind turbine structural steels with high elastic modulus and excellent comprehensive mechanical properties has become an urgent need for the current development of offshore wind power equipment materials technology. By constructing a series of high elastic modulus steel products ranging from low to high strength grades, and configuring material performance according to the strength and stiffness requirements of different structural parts such as the upper transition section of various offshore wind turbines, maintenance platform supports, pile foundation uppers, pile foundation nodes, X-joints, suction cylinders, jacket structures, and tendon tubes, it is possible to significantly improve structural response control capabilities, enhance service stability, and provide key material support for offshore wind power equipment to move towards higher power, larger scale, and farther sea areas. The construction of this material system will play a vital role in improving the operational reliability and industrial competitiveness of offshore wind power equipment.
[0007] Public reports on related patents:
[0008] Chinese invention patent CN114686783B discloses a high-elasticity modulus age-hardening high-speed steel material and its preparation method. It employs a multi-element high-alloy system, using solid solution strengthening by adding Cr, V, Ni, and the non-metallic element N, as well as synergistic particle reinforcement by adding nitrides. Combined with powder metallurgy + high-temperature solid solution + aging treatment processes, a high-elasticity modulus age-hardening high-speed steel with an elastic modulus greater than 240 GPa is obtained. This method uses high-temperature heat treatment to form a dispersed phase to enhance stiffness, making it suitable for the cutting tool and mold fields. However, due to its primary use of powder metallurgy, its complex composition, high processing temperature, and high cost make it difficult to meet the engineering adaptability requirements of wind power structural steel in large-scale continuous casting-hot rolling production and low-cost manufacturing.
[0009] Regarding the performance requirements of steel used in offshore wind turbine structures, numerous inventions in recent years have focused on optimizing the composition system and heat treatment process to improve the fracture toughness, thickness-direction properties, and resistance to aging. For example, Chinese invention patent CN111809117A discloses a high fracture toughness, low aging sensitivity offshore wind turbine steel and its production method. It employs a C-Si-Mn-Nb-Ti-Mo-Ni composition system and utilizes a process path of continuous casting + two-stage controlled rolling + UFC / ACC controlled cooling + hot straightening + heat sink cooling to achieve excellent CTOD and low-temperature aging properties. The maximum thickness of the finished product reaches 130 mm, and the maximum weight of a single continuously cast billet reaches 32 tons. This solution focuses on improving the safety of welded joints and service aging stability. While it significantly controls the microstructure and toughness, it does not propose a design mechanism to increase the material's elastic modulus to enhance structural stiffness.
[0010] Chinese invention patent CN111676424A discloses a method for producing heavy-duty, extra-thick offshore wind turbine steel. By employing a process route of continuous casting + heating + controlled rolling + pre-straightening + controlled cooling + slow cooling, it achieves a good balance of strength and toughness, as well as stable microstructure, up to a maximum thickness of 130mm. This invention achieves homogenized microstructure by optimizing the rolling reduction rate and cooling rate, while also possessing excellent weldability to meet the requirements of heavy-duty and extra-thick specifications. However, its main technical approach focuses on thickness, yield, and toughness control, neglecting stiffness design and failing to address the high elastic modulus properties of the steel required for modal response regulation of offshore wind turbine structures.
[0011] Chinese invention patent CN114807761A discloses a high-ductility EH36 grade marine engineering steel and its manufacturing method. It employs a low-carbon, low-alloy composition system combined with smelting, continuous casting, and controlled rolling processes to obtain EH36 grade marine engineering steel with a yield strength ≥360MPa, tensile strength 490~630MPa, elongation ≥32%, and impact energy ≥200J at -40℃. This method focuses on improving the ductility, low-temperature toughness, and fracture safety of marine engineering steel, but does not involve increasing the elastic modulus of the steel plate through in-situ generation of high-modulus reinforcing phases, nor does it use the elastic modulus as a constraint on the stiffness design of offshore wind power structures.
[0012] Chinese invention patent CN112176248A discloses a low-carbon equivalent extra-thick DH36 offshore wind power steel plate and its production method, involving DH36 offshore wind power steel plates with a specification of 50-100mm and delivered in TMCP condition. This solution obtains extra-thick steel plates meeting the DH36 strength level through low-carbon equivalent composition design and controlled rolling and cooling processes. It focuses on solving the problems of low carbon equivalent, weldability, and low-temperature toughness of thick-gauge offshore wind power steel plates, but does not propose improving the material's elastic modulus through in-situ TiB2 reinforcement.
[0013] Chinese invention patent CN111455255B discloses a method for preparing 80-100mm thick EH36 steel for offshore wind power. The method involves processes such as composition control, billet heating, controlled rolling, and normalizing to obtain EH36 grade thick offshore wind power steel. This solution focuses on addressing the issues of microstructure uniformity and strength-toughness matching in ultra-thick EH36 steel, but it does not address high elastic modulus or propose particle reinforcement designs to improve the stiffness of wind turbine structures.
[0014] Chinese invention patent CN106148833A discloses a normalized 36 kg grade marine engineering steel plate and its production method. The 36 kg grade marine engineering steel plate is obtained through processes such as smelting, rolling, cooling, and normalizing. This solution mainly focuses on the strength, toughness, and production process stability of conventional 36 kg grade marine engineering steel, without considering improvements in elastic modulus, resistance to seawater splash corrosion, and the synergistic design of Ti / B in-situ reinforcement as technical objectives.
[0015] In summary, current high-elasticity modulus steel and offshore wind power steel, as well as their manufacturing technologies, have the following shortcomings:
[0016] 1. Currently, most publicly available high-elasticity modulus steel technologies employ high alloying elements, intermetallic compounds, and complex powder metallurgy processes, which increases the manufacturing cost of materials and makes it difficult to meet the needs of mass production of offshore wind power equipment.
[0017] 2. Existing high elastic modulus steels are mainly used in automobiles, cutting tools, molds and dies, etc., mainly in cold-rolled thin plates or small-sized products. They do not involve the service performance required in marine environments, such as low-temperature impact toughness and corrosion resistance. They are difficult to meet the thickness specifications of large structural components for offshore wind power, and it is also impossible to evaluate the service safety of materials in marine environments.
[0018] 3. Existing research on offshore wind power steel and marine engineering structural steel of similar strength grade mainly focuses on strength, low temperature toughness, Z-direction performance, weldability, ductility or production stability of thick specifications. The modulus of elasticity has not yet been used as a clear material indicator for the stiffness and modal response of wind power structures. This makes it difficult to meet the structural safety and stiffness requirements brought about by the further development of offshore wind power equipment towards deep sea, high power and large size. Summary of the Invention
[0019] The purpose of this invention is to overcome the above-mentioned problems and deficiencies and provide a 36kg grade offshore wind power steel with high elastic modulus, yield strength ≥360MPa, tensile strength 490~630MPa, elongation after fracture ≥21%, Charpy impact energy ≥100J at -20℃, resistance to seawater splash corrosion, and good low-temperature toughness and elongation, as well as its production method. It is suitable for the lower section of offshore wind turbine towers, the upper part of jacket structures, and other structures.
[0020] The objective of this invention is achieved as follows:
[0021] A 36kg grade offshore wind power steel with high elastic modulus has the following composition by weight percentage: C: 0.035%~0.045%, Si: 0.15%~0.25%, Mn: 0.80%~0.90%, Cr: 1.5%~2.5%, Cu: 0.25%~0.40%, Nb: 0.02%~0.03%, Ti: 1.5%~2.5%, B: 0.6%~1.2%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
[0022] Furthermore, in the wind power steel, -0.6%≤Ti-2.22×B≤0.6%.
[0023] Furthermore, the Cr / Cu ratio in the wind power steel is 3.75~10.00.
[0024] Furthermore, the microstructure of the wind power steel includes ferrite, bainite, and pearlite, with fine TiB2 hard reinforcing particles uniformly dispersed throughout the steel.
[0025] Furthermore, the ferrite volume percentage is 80%~90%, the ferrite grain diameter is 11~16μm, the pearlite lamellar spacing is ≤200nm, and the TiB2 hard reinforcing particles in the wind power steel have a volume fraction ≥3%, an average particle size <5μm, and a distribution density of 1500~2500 particles / mm².
[0026] The steel plate used for offshore wind power has an elastic modulus ≥220GPa, yield strength ≥360MPa, tensile strength 490~630MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and a thickness range of 20~60mm.
[0027] The rationale for the design of the components in this invention is as follows:
[0028] The overall design concept of this invention is as follows: First, focusing on the coupled requirements of stiffness, low-temperature toughness, and resistance to seawater splash corrosion for medium-thick steel plates such as the lower section of the 36kg offshore wind turbine tower and the upper part of the jacket, a design with low C and Mn content is selected. The low C and Mn system ensures the proportion of ferrite phase in the final microstructure of the steel plate, compensating for the plasticity loss caused by the introduction of hard reinforcing phase particles. Second, the addition of Cr and Cu effectively improves the resistance of the steel plate to seawater splash corrosion and extends the service life of offshore wind turbine steel. Third, Nb microalloying significantly inhibits austenite grain growth and promotes ferrite refinement, thereby improving the comprehensive strength, toughness, and microstructure uniformity of the steel plate. Fourth, Ti and B elements are introduced, and by controlling the Ti to B ratio -0.6%≤Ti-2.22×B≤0.6%, the reinforcing phase is formed in situ during the solidification of the molten steel and the subsequent evolution of the solidification microstructure and remains fine and dispersed. By utilizing high-modulus particles to constrain composition, inclusions, solidification flow, rolling deformation, and phase transformation structure, an elastic modulus gain is achieved under 36kg-level strength, toughness, and corrosion resistance conditions, thus meeting the requirements of high-rigidity steel plates for large-scale offshore wind power structure design.
[0029] Carbon (C) is one of the fundamental elements ensuring the strength of the steel plate matrix. Although this invention uses a low-carbon system, C can still synergistically enhance the strength of the steel plate through solid solution strengthening and microalloying precipitation strengthening mechanisms. In this invention, the design role of C content is mainly reflected in the following three aspects: First, it contributes to the strength of the steel plate matrix through solid solution strengthening; second, it provides the necessary carbon source for the formation of NbC precipitates by working together with microalloyed Nb elements, thus pinning grain boundaries in the form of NbC precipitation to hinder austenite grain coarsening and providing favorable conditions for final microstructure refinement control; third, based on the perspective of phase structure control, it adopts the lowest possible C content to increase the proportion of soft ferrite phase, thereby compensating for the plasticity problem caused by the introduction of elastic modulus-enhancing phase particles. Therefore, considering the purpose of the invention and the overall performance, the preferred C content is controlled at C: 0.035%~0.045%.
[0030] Si is the main deoxidizing component in the steelmaking process. Si in solid solution form can increase strength, ductile-brittle transition temperature, elastic limit and fatigue strength. In order to obtain sufficient deoxidation effect, it must contain more than 0.10%. However, if the upper limit is too high, it will reduce the toughness of the base material and welded parts and have an adverse effect on the surface quality of the steel. Therefore, it is preferred to control the Si content at 0.15%~0.25%.
[0031] Mn: Mn is an essential element for ensuring the strength and toughness of steel. In this invention, the role of Mn is mainly reflected in two aspects: first, it contributes to the strength of the steel plate matrix through solid solution strengthening; second, Mn expands the austenite region, which can improve the hardenability of steel and is beneficial for controlling the pearlite lamellar spacing during rapid Acc cooling of the steel plate. However, Mn is prone to segregation in steel, especially at 1 / 4 and 1 / 2 thickness of medium-thick steel plates, resulting in a significant reduction in low-temperature toughness and even delamination of the impact fracture surface. More importantly, as the Mn content increases, the corrosion resistance of the steel plate decreases. Therefore, considering both material mechanics and corrosion resistance, the preferred Mn content range is controlled between 0.80% and 0.90%.
[0032] Cr: Cr is an effective element for improving the corrosion resistance of steel. The addition of Cr to steel has a significant impact on the electrochemical process of steel. Cr can inhibit the anodic dissolution process in the electrochemical process, and the corrosion potential of the steel matrix shifts positively. The higher the amount of Cr added, the more obvious the inhibitory effect on the anodic process. In the rust layer, Cr can form Cr2O3 and Cr(OH)3 products with better stability and corrosion resistance. On the other hand, Cr can promote the formation of α-FeOOH in the rust layer, and some of it will also be mixed with α-FeOOH and Fe3O4 to form thermodynamically more stable α-(Fe,Cr)OOH and FeCr2O4. Under the combined effect of these two factors, the stability and protective properties of Cr-containing steel rust layers are greatly improved. The Cr-containing products in the rust layer can improve the original loose and porous network structure of the rust layer, providing more nucleation sites. Rust particles gradually become spheroidized and refined, which is conducive to the subsequent tight agglomeration and fusion between particles, reducing defects in the rust layer. Over time, the rust layer structure gradually becomes denser, which can effectively prevent the penetration of corrosive Cl- ions from seawater splash. In addition, Cr is also an effective element for improving the strength of steel plates. However, excessive Cr can cause a decrease in weldability. Therefore, the Cr content in this invention is controlled at 1.5% to 2.5%.
[0033] Cu: Cu is an essential element for improving the corrosion resistance of steel in marine environments. During the corrosion process, it accumulates in the inner rust layer in the form of CuO, effectively isolating corrosive media, reducing the corrosion-promoting effect of chloride ions, and increasing the polarization resistance of the steel, thus enhancing the protective properties of the rust layer and improving the corrosion resistance of the steel in marine environments. In terms of mechanical properties, Cu can improve the strength of steel plates with minimal impact on their low-temperature toughness; however, excessive Cu addition will cause fine, dispersed ε-Cu precipitation during hot rolling or normalizing, impairing the low-temperature toughness of the steel plate and potentially leading to copper embrittlement, casting cracks, and liquid precipitation defects. Therefore, considering both material mechanics and corrosion resistance, the Cu content in this invention is controlled within the range of 0.25% to 0.40%. Preferably, the Cr / Cu mass ratio is controlled within the range of 3.75 to 10.00. When the Cr / Cu ratio is too low, the inhibitory effect of Cr on anodic dissolution and the stabilizing effect of dense rust layers such as Cr2O3 and Cr(OH)3 are insufficient, and the relative enrichment of Cu easily increases the risk of copper embrittlement, hot working cracks, and ε-Cu precipitation. When the Cr / Cu ratio is too high, the excessive Cr content easily reduces weldability and increases alloy costs, and Cu enriches in the inner rust layer, blocking Cl. - The synergistic effect of penetration and increased polarization resistance is insufficient. Controlling the Cr / Cu ratio within the above range can balance the two effects of Cr stabilizing the rust layer and Cu enriching the inner rust layer, thereby improving resistance to seawater splash corrosion while also taking into account toughness, weldability, and cost control.
[0034] Nb: Nb is an important microalloying element used in this invention for microstructure refinement and performance enhancement. It has a strong affinity for non-metallic elements such as C, N, and O, and can form stable fine precipitates such as NbC, NbN, or Nb(C,N). During the hot working of steel plates, Nb effectively controls the microstructure after rolling by inhibiting austenite grain growth, delaying dynamic recrystallization, and promoting ferrite phase transformation, significantly improving the refinement and uniformity of the microstructure, thereby enhancing the strength and toughness matching level of the steel plate. Especially under the single-pass high reduction rolling and low-temperature homogenization strategy adopted in this invention, precipitates such as NbC can act as grain pinning points, effectively improving rolling stability and controlling the final rolled microstructure morphology. Considering the good stability and grain control ability of Nb in the continuous casting + TMCP process, the Nb content is preferably controlled at 0.02%~0.03% in this invention to give full play to its microalloying refinement and strengthening effect, while avoiding coarsening of precipitates and increased costs due to excessive addition.
[0035] Ti: Ti is a key alloying element in the steel of this invention, mainly used to react in situ with boron (B) during the solidification of molten steel to generate TiB2 reinforcing particles. TiB2 has a high melting point, hexagonal crystal structure, and extremely high elastic modulus (approximately 565 GPa). After being finely dispersed in the matrix, it can significantly improve the overall elastic modulus and specific modulus of the steel plate, meeting the service requirements of high-rigidity materials for large offshore wind power structures. Based on the design specifications of the 36kg-grade structural steel plate of this invention (yield strength ≥ 360 MPa, elastic modulus ≥ 220 GPa), the elastic modulus of the conventional carbon steel matrix (approximately 210 GPa) is increased by at least 10 GPa, introducing a TiB2 reinforcing phase with a volume fraction of approximately 3% or more. The Ti content design needs to comprehensively consider the density and molar composition ratio of TiB2, as well as the in-situ reaction efficiency in the molten steel, taking into account potential reaction losses and element segregation in industrial production, to ensure sufficient TiB2 particle formation, controlled size, and uniform distribution, while avoiding Ti residue or the formation of unfavorable inclusions. Furthermore, Ti in this system also functions as a microalloying strengthener, forming fine precipitates such as TiN and TiC with impurities N and C. During hot working, Ti synergistically inhibits austenite grain growth and promotes grain refinement, thereby improving the uniformity of the steel plate's microstructure and its strength-toughness balance. In summary, Ti in this invention serves as both a core element for strengthening phase formation and a microstructure control function. Its content design needs to achieve an optimal balance between strengthening efficiency and metallurgical stability, preferably controlled within the range of 1.5% to 2.5%.
[0036] B: Element B is an essential alloying element for constructing the reinforcing phase TiB2 in the steel plate of this invention. Its main function is to react with Ti in situ during the solidification of molten steel to generate TiB2 reinforcing particles, thereby improving the elastic modulus and specific modulus of the steel plate. TiB2 has a high elastic modulus and excellent thermal stability, and its strengthening effect is closely related to its volume fraction, size, and distribution in the matrix. To achieve the performance target of an elastic modulus ≥220 GPa for the 36 kg grade steel plate of this invention while maintaining good strength and toughness, a TiB2 reinforcing phase with a volume fraction of approximately 3%~4% is introduced. The amount of B added must be synergistically matched with the Ti content. Taking into account the stoichiometry, molar mass, and reaction efficiency of TiB2, this invention aims to achieve sufficient TiB2 formation while avoiding residual segregation of Ti and B or the formation of other brittle compounds. This is achieved by controlling the mass ratio of Ti to B within the range of -0.6% ≤ Ti - 2.22 × B ≤ 0.6%, ensuring that TiB2 is formed in situ, with controlled particle size and uniform distribution. This also avoids the precipitation of non-target phases or deterioration of the steel plate's plasticity due to excessive Ti or B. Furthermore, trace amounts of B in steel also strengthen grain boundaries, providing microstructural support for the stable service of materials in marine environments. In summary, B in this invention serves both as a reactive component for the formation of the TiB2 reinforcing phase and as an auxiliary element for regulating the microstructure and properties of the steel plate. Its content design must be closely coordinated with the Ti content, comprehensively considering reaction efficiency, nucleation behavior, and metallurgical compatibility. The preferred content range is 0.6% to 1.2%.
[0037] P (Polyphosphate) is a typical harmful impurity element in steel. During cooling and solidification, it easily segregates in the center of the slab and accumulates at grain boundaries to form a brittle thin film structure, significantly reducing the low-temperature impact toughness and ductility of the steel plate. It also exacerbates the crack sensitivity of the weld heat-affected zone, affecting the weldability of the steel. Although P can improve the corrosion resistance of steel under certain conditions, its weakening effect on fatigue performance and overall ductility and toughness is more significant, making it difficult to use as a corrosion-resistant alloying element in high-strength and toughness structural steels. The steel plate of this invention has improved its corrosion resistance to seawater splash environment by adding Cr and Cu elements, thus it does not rely on P for corrosion resistance. To ensure the low-temperature impact performance, ductility, and weld safety of the steel plate, this invention strictly controls the P content to no more than 0.01% to ensure overall service reliability.
[0038] S: S is a typical harmful impurity element in steel, readily reacting with Mn to form low-melting-point MnS inclusions. Especially during hot rolling, these inclusions tend to extend along the rolling direction, forming banded structures that become microcrack initiations under fatigue loads or low-temperature impact conditions, severely impairing the steel plate's fatigue resistance, impact toughness, and thickness-direction (Z-direction) properties. Furthermore, S inclusions are also detrimental to the stability and crack resistance of the subsequent weld zone. To ensure good ductility and toughness in the steel plate, this invention further controls the purity of the molten steel based on a low-Mn design, preferably with an S content ≤0.002%. Under certain non-critical service conditions or without Z-direction property (i.e., thickness-direction plasticity) requirements, an S content of ≤0.004% is also acceptable.
[0039] Als: As a necessary deoxidizing and grain-refining element added in this invention, the added content is above 0.01%, but exceeding 0.08% can easily cause hot cracking in the cast billet, and at the same time reduce the toughness of the steel. The Als content is controlled between 0.015% and 0.025%.
[0040] The present invention also provides an industrial production method for 36kg-grade offshore wind power steel with high elastic modulus, including smelting, continuous casting, heating, controlled rolling, and controlled cooling.
[0041] (1) Smelting:
[0042] This invention involves smelting according to the designed alloy composition range, using converter or electric furnace smelting, LF refining, and RH vacuum cycle refining.
[0043] During the smelting process, the content of each alloying element and the purity of the molten steel are precisely controlled. In the LF refining stage, dephosphorization is performed until the P content is no higher than 0.01%, desulfurization until the S content is no higher than 0.002%, and the total oxygen content is controlled below 20 ppm. During the LF refining alloying stage, Ti and B elements are precisely added, ensuring that the mass ratio of Ti to B meets the condition -0.6% ≤ Ti – 2.22 × B ≤ 0.6%, so as to generate TiB2 reinforcing particles with an average particle size of no more than 5 μm in situ during the solidification process. Simultaneously, argon blowing is continuously performed for no less than 40 minutes during LF refining to promote the homogenization of elements in the molten steel and prevent the coarsening of TiB2 particles, ensuring uniformity of composition and particle distribution. The RH refining time is ≥30 minutes. At the end of the RH refining process, the alloy composition and temperature of the molten steel are precisely adjusted, and the superheat at tapping is controlled below 25℃, providing stable metallurgical conditions for subsequent continuous casting processes.
[0044] (2) Continuous casting:
[0045] The continuous casting process is adopted, with protective pouring throughout the process. The slab thickness is 250~300mm, and the casting speed is controlled within the range of 0.8~1.2m / min. The liquid level fluctuation in the crystallizer is controlled within ±3mm. To promote the refinement and uniform dispersion of TiB2 reinforcing particles, electromagnetic stirring (M-EMS) is installed in the continuous casting crystallizer, with the stirring current preferably controlled at 550~600A and the frequency at 5~7Hz. In the secondary cooling section, flexible electromagnetic stirring (F-EMS) is used to further optimize the fluidity of the molten steel and avoid grain boundary segregation and TiB2 particle agglomeration and coarsening. The preferred current for the flexible electromagnetic stirring F-EMS in the secondary cooling section is 460~520A and the frequency is 3~5Hz. The secondary cooling section employs a zoned cooling method, which is preferred. The specific water content in the foot roll section, bending section, and straightening section is controlled at 0.28~0.34L / kg, 0.20~0.27L / kg, and 0.12~0.17L / kg, respectively, and is adjusted in conjunction with the F-EMS to ensure uniform growth of the solidified shell of the billet, reducing the risk of center segregation, shrinkage cavities, and internal cracks. After the billet exits the mill, a slow cooling device is used to reduce the internal stress gradient, further improving the billet quality and laying the foundation for subsequent controlled rolling and controlled cooling processes.
[0046] (3) Heating:
[0047] To prevent the billet from overheating during the heating process, a low-temperature heating + short-time heat preservation process is adopted. Under the premise of ensuring austenite homogenization, the original austenite grain size is controlled. The heating temperature is controlled at 1100~1150℃, the total heating time is controlled at 4~5h, and the furnace exit temperature is controlled at 1080~1120℃.
[0048] (4) Rolling:
[0049] After heating, the continuously cast billet is subjected to a three-stage controlled rolling process. The first stage involves rolling at an initial temperature of 980–1050℃ within the austenite recrystallization temperature range, with a maximum rolling torque of 3100 kNm and a cumulative reduction rate ≥45%, including at least one high-reduction pass with a single-pass reduction rate ≥25%. This stage utilizes the high-reduction deformation in the recrystallization zone to break up the as-cast microstructure, promoting austenite phase deformation nuclei, refining the γ phase and storing energy, creating conditions for subsequent γ→α phase transformation, and improving the uniformity of TiB2 reinforcing particle distribution along the thickness direction. The second stage involves rolling at an initial temperature of 860–890℃ within the non-recrystallization temperature range of austenite, maintaining an average single-pass reduction rate above 20% to provide more nucleation points and increase the nucleation rate under non-recrystallization conditions, further refining the microstructure and increasing the ferrite proportion. The third stage of rolling begins at a rolling temperature of 780~800℃, and is carried out in the austenite + ferrite two-phase region. The cumulative reduction rate is controlled at 18%~24%, and the target thickness is achieved.
[0050] (5) Straightening:
[0051] After rolling, the steel plate needs to be straightened to improve its flatness and prevent problems such as warping during the cooling process.
[0052] (6) Cooling:
[0053] After straightening, the steel plate, at a temperature of 730~750℃, enters a rapid laminar flow cooling system with an average cooling rate of 5~8℃ / s. The reddening temperature is controlled at 560~600℃ to control the composition and size of the phase transformation microstructure, resulting in a multiphase microstructure of ferrite + bainite + pearlite. After cooling, the steel plate undergoes slow cooling for ≥24 hours.
[0054] Through the above-mentioned smelting, continuous casting and TMCP process control, the uniformity of the microstructure of the final steel plate, the grain size of the reinforcing phase, the grain size and the proportion of each phase are ensured to meet the design requirements. The volume percentage of ferrite is 80%~90%, the average grain size of ferrite is 9~10, the interlamellar spacing of pearlite is ≤200nm, the volume fraction of TiB2 reinforcing phase particles is not less than 3%, the average particle size is <5μm, and the distribution density is 1500~2500 particles / mm².
[0055] The beneficial effects of this invention are as follows:
[0056] (1) This invention adopts a composition design of low C, Mn+Cr-Cu seawater splash corrosion resistant alloying + Ti-B in-situ precipitation reinforcement phase + Nb microalloying. On the basis of ensuring high ferrite ratio and good plasticity reserve in the low C, low Mn system, Cr and Cu are added to form a stable and uniform corrosion resistant rust layer, and the microstructure is refined by Nb microalloying.
[0057] (2) During the refining and alloying stage, the Ti and B mass ratio is precisely controlled to -0.6%≤Ti–2.22×B≤0.6%, and fine and dispersed TiB2 particles are formed in situ in the low C-Mn-Cr / Cu-Nb corrosion-resistant matrix, providing an increase in elastic modulus. The distribution of the reinforcing phase is optimized by combining electromagnetic stirring (M-EMS) in the continuous casting crystallizer and flexible electromagnetic stirring (F-EMS) in the second cooling section. Combined with low temperature homogenization + three-stage controlled rolling + controlled cooling process, the steel plate matrix is finally obtained as a ferrite + bainite + pearlite multiphase structure; the ferrite volume fraction is 80%~90%, the average grain size is 9~10, the pearlite lamellar spacing is ≤200nm, and TiB2 hard reinforcing particles with a volume fraction greater than 3% are dispersed, with an average particle size of <5μm and a distribution density of 1500~2500 particles / mm².
[0058] (3) The microstructure of the steel plate is controlled throughout the entire process of steelmaking electromagnetic stirring (EMS), low temperature homogenization + short time heat preservation continuous casting billet heating and single-pass high reduction rolling, and finally a 36kg grade high elastic modulus medium and thick plate product with strong plasticity, stable toughness and resistance to seawater splash corrosion is obtained.
[0059] (4) The steel plate of this invention has an elastic modulus ≥220 GPa, yield strength ≥360 MPa, tensile strength 490~630 MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100 J, and an average corrosion rate (g / m²) of the steel plate under the condition of 3.5% neutral NaCl solution for a corrosion period of 168 h. 2 The average corrosion rate (g / m³) over a corrosion cycle of 360 hours is 0.75~0.79. 2 With a modulus of elasticity (h) of 0.70~0.75, this steel plate possesses high elastic modulus, good ductility, low-temperature toughness, and resistance to seawater splash corrosion. It is suitable for structures such as the lower section of offshore wind turbine towers and the upper part of jacket structures, meeting the requirements for long-term safe operation in seawater splash environments. The medium-thick steel plate prepared by this invention for large offshore wind turbines exhibits high elastic modulus, resistance to seawater splash corrosion, good elongation, and low-temperature toughness, making it suitable for structures such as the lower section of towers and the upper part of jacket structures. Its comprehensive performance meets the requirements for long-term service of offshore wind turbines. Attached Figure Description
[0060] Figure 1 This is the metallographic microstructure at the 1 / 4 thickness position of Embodiment 1 of the present invention. Detailed Implementation
[0061] The present invention will be further illustrated below through examples.
[0062] The elemental composition of the wind power steel of this invention, by mass percentage, is as follows: C: 0.035%~0.045%, Si: 0.15%~0.25%, Mn: 0.80%~0.90%, Cr: 1.5%~2.5%, Cu: 0.25%~0.40%, Nb: 0.02%~0.03%, Ti: 1.5%~2.5%, B: 0.6%~1.2%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
[0063] Furthermore, in the wind power steel, -0.6%≤Ti-2.22×B≤0.6%.
[0064] Furthermore, the Cr / Cu ratio in the wind power steel is 3.75~10.00.
[0065] Furthermore, the microstructure of the wind power steel includes ferrite, bainite, and pearlite, with fine TiB2 hard reinforcing particles uniformly dispersed throughout the steel.
[0066] Furthermore, the ferrite volume percentage is 80%~90%, the ferrite grain diameter is 11~16μm, the pearlite lamellar spacing is ≤200nm, and the TiB2 hard reinforcing particles in the wind power steel have a volume fraction ≥3%, an average particle size <5μm, and a distribution density of 1500~2500 particles / mm².
[0067] The steel plate used for offshore wind power has an elastic modulus ≥220GPa, yield strength ≥360MPa, tensile strength 490~630MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and a thickness range of 20~60mm.
[0068] According to the component ratio of the technical solution, the embodiments of the present invention carry out smelting, continuous casting, heating, controlled rolling and controlled cooling.
[0069] Heating: The continuous casting billet is heated at 1100~1150℃ for a total duration of 4~5 hours;
[0070] Controlled rolling: A three-stage controlled rolling process is adopted after the continuous casting billet is heated;
[0071] The first stage of rolling starts at a temperature of 980~1050℃ and has a cumulative reduction rate of ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%.
[0072] The second-stage rolling temperature is 860~890℃, and the average single-pass reduction rate is ≥20%.
[0073] The third stage of rolling begins at a rolling temperature of 780~800℃, with a cumulative reduction rate of 18%~24%, and is rolled to the target thickness.
[0074] Controlled cooling: After straightening, the steel plate is initially cooled at 730~750℃ and then enters a rapid laminar flow cooling system at a cooling rate of 5~8℃ / s, with a reddening temperature of 560~600℃. After cooling, the steel plate is subjected to slow cooling for ≥24 hours.
[0075] Furthermore; smelting includes converter or electric furnace smelting, LF refining, and RH refining;
[0076] During the LF refining stage, P ≤ 0.01% and S ≤ 0.002% are controlled, and before the RH refining is completed, the total oxygen in the molten steel is controlled to ≤ 20 ppm.
[0077] Ti and B elements are added during the LF refining and alloying stage, and the argon blowing time during the refining process is ≥40min.
[0078] RH refining time ≥30min, tapping superheat ≤25℃;
[0079] Furthermore, the continuous casting process also includes electromagnetic stirring technology. The electromagnetic stirring current in the continuous casting crystallizer is 550~600A and the frequency is 5~7Hz. The second cooling section adopts electromagnetic stirring at the solidification end, with an F-EMS current of 460~520A and a frequency of 3~5Hz.
[0080] Furthermore, the secondary cooling section adopts a zoned cooling method, with the specific water content in the foot roller section, bending section, and straightening section controlled at 0.28~0.34L / kg, 0.20~0.27L / kg, and 0.12~0.17L / kg, respectively; the billet is slowly cooled after exiting the machine.
[0081] The present invention provides a method for testing the microstructure and properties of steel used in offshore wind power.
[0082] (1) Statistical method for reinforcing phase: The volume fraction, average size, and distribution density of the TiB2 reinforcing phase in steel were obtained quantitatively through scanning electron microscopy (SEM) images. At magnifications of 5000–10000, more than 10 representative fields of view were randomly selected, with each field of view having a statistical area of no less than 1000 μm². Particle boundaries were identified and automatically counted using image analysis software to obtain the number of particles and their equivalent diameter distribution; the volume fraction was obtained by converting the proportion of the particle's projected area. All results were taken as the average value of all fields of view, and the relative error of the measurement was limited to no more than ±10% to ensure the reliability and repeatability of the results.
[0083] (2) Detection of average pearlite lamellar spacing: The metallographic sample after mechanical grinding, polishing and etching with 4% nitric acid alcohol solution was observed using a scanning electron microscope (SEM). The sampling locations were representative areas at 1 / 4 and 1 / 2 of the steel plate thickness. At a magnification of 10,000 to 20,000, no less than 10 pearlite clusters or representative fields of view were randomly selected, and no less than 5 measurement lines were drawn in each field of view along the direction perpendicular to the pearlite lamellars. The effective length L of each measurement line and the number of lamellar intervals n it traversed were recorded. The lamellar spacing of a single measurement line was calculated according to s=L / n, where L was converted to nm according to the image scale. No less than 50 effective lamellar spacing data were collected for each example. Areas that were obviously non-pearlite, areas with severe lamellar bending and areas with incomplete image edges were removed. The arithmetic mean was taken as the average pearlite lamellar spacing, and the relative error of the measurement was controlled within ±10%.
[0084] (3) Elastic modulus testing: The method specified in GB / T 228.1-2021 or ASTM E111-17 shall be adopted. A standard tensile specimen (parallel length 50 mm, diameter 12.5 mm) in the rolling direction shall be taken and stretched at a loading rate of 2 mm / min under room temperature conditions using an extensometer with an accuracy of 0.5 or higher. The elastic modulus shall be calculated based on the slope of the initial linear segment of the stress-strain curve, and the average value of 3 parallel specimens shall be taken as the result.
[0085] (4) Seawater splash corrosion resistance test: Accelerated corrosion tests were conducted using laboratory periodic immersion corrosion tests to simulate the seawater splash environment. Accelerated corrosion tests were performed on the embodiments of this invention, with a 40mm thick DH36 steel plate used as a comparative example. The test solution was a 3.5% neutral NaCl solution. The test environment temperature was 40±2℃, the solution temperature was 35±2℃, and the humidity was 60±5%RH. The sample rotation speed was 3r / h. Other conditions were performed according to GB / T 19746 "Corrosion of Metals and Alloys - Periodic Immersion Tests with Salt Solutions". Each wet-dry cycle lasted 60min (10min immersion, 50min drying), and the periodic immersion corrosion cycles were 168h and 360h, respectively. The average corrosion rate (g / m³) was calculated using the weight loss method. 2 •h) Evaluate the corrosion resistance of the steel plate.
[0086] The compositions of the steels in the embodiments of the present invention and the comparative steels are shown in Table 1. The main process parameters for smelting and continuous casting of the steels in the embodiments of the present invention are shown in Table 2. The zonal cooling parameters for the secondary cooling section of the continuous casting of the steels in the embodiments of the present invention are shown in Table 3. The main process parameters for heating and the first and second stage controlled rolling of the steels in the embodiments of the present invention are shown in Table 4. The main process parameters for the third stage controlled rolling and controlled cooling of the steels in the embodiments of the present invention are shown in Table 5. The mechanical properties of the steels in the embodiments of the present invention and the comparative steels are shown in Table 6. The seawater splash corrosion resistance rate (g / m³) of the steels in the embodiments of the present invention and the comparative steels is also shown in Table 6. 2 (h) See Table 7. The microstructure of steel in the embodiments of the present invention is shown in Table 8.
[0087] Table 1. Composition (wt%) of the steel in the embodiments of the present invention and the comparative steel.
[0088] 1 0.035 0.22 0.83 1.57 0.26 0.022 1.6 0.72 0.022 6.04 0.0016 2 0.042 0.20 0.81 2.35 0.34 0.027 2.4 1.06 0.024 6.91 0.0468 3 0.045 0.24 0.85 2.03 0.29 0.030 2.2 0.95 0.018 7.00 0.091 4 0.038 0.18 0.89 1.99 0.37 0.029 2.1 0.93 0.024 5.38 0.0354 5 0.037 0.19 0.84 1.82 0.28 0.023 1.8 0.81 0.016 6.50 0.0018 6 0.042 0.23 0.87 1.56 0.38 0.025 1.5 0.67 0.019 4.11 0.0126 Comparative Example 0.076 0.27 1.52 - - 0.032 0.012 - 0.035 - -
[0089] In the embodiments of the present invention, the steel contains P: ≤0.01%, S: ≤0.002%, N: ≤0.0030%, and O: ≤0.0020%.
[0090] Table 2 Main process parameters for steel smelting and continuous casting in the embodiments of the present invention.
[0091] 1 45 32.0 21 250 550 5 460 4 0.9 2 45 34.0 21 250 600 7 520 5 0.8 3 50 35.0 23 250 600 7 500 4 1.1 4 50 33.5 24 300 550 6 460 4 0.9 5 50 36.0 21 300 600 5 470 4 1.2 6 50 31.5 20 300 600 5 460 3 1.0
[0092] Table 3. Zoned cooling parameters for the secondary cooling section of continuous casting steel according to embodiments of the present invention.
[0093] 1 0.28 0.20 0.12 2 0.34 0.27 0.17 3 0.31 0.23 0.14 4 0.30 0.22 0.13 5 0.33 0.26 0.16 6 0.29 0.21 0.12
[0094] Table 4. Main process parameters for steel heating and one- and two-stage controlled rolling in the embodiments of the present invention.
[0095] 1 1130 4.5 1028 48 30 878 20 2 1140 4.5 1035 50 32 882 21 3 1140 4.5 1032 47 31 875 21 4 1150 5.0 1050 46 29 872 22 5 1150 5.0 1044 49 34 876 24 6 1150 5.0 1047 51 33 866 25
[0096] Table 5. Main process parameters for three-stage controlled rolling and controlled cooling of steel in the embodiments of the present invention.
[0097] 1 781 764 20 730 8 569 25 2 783 766 22 735 8 577 25 3 785 770 19 740 7 571 26 4 797 783 21 740 6 583 26 5 792 786 24 745 6 589 27 6 793 784 18 750 5 576 27
[0098] Table 6 Mechanical properties of the steels in the embodiments of the present invention and the comparative steels
[0099] 1 21 221 410 566 24 136 2 35 228 437 571 23 117 3 35 226 431 569 22 141 4 40 225 429 567 25 125 5 55 223 407 573 25 141 6 60 220 398 553 28 152 Comparative Example 40 206 386 511 25 211
[0100] Table 7. Seawater splash corrosion resistance rates of the steels in the embodiments of the present invention and the comparative steels (g / m³) 2 ·h)
[0101] 1 0.7921 0.7428 2 0.7537 0.7065 3 0.7713 0.7210 4 0.7721 0.7205 5 0.7674 0.7159 6 0.7869 0.7356 Comparative Example 1.1035 1.0267
[0102] Table 8. Steel microstructure of embodiments of the present invention
[0103] 1 85.4 5.1 12.0 168 3.2 3.6 1630 2 81.3 5.8 11.9 148 4.1 4.4 2103 3 82.6 5.6 12.2 154 3.8 4.1 1937 4 83.1 5.3 12.1 162 3.6 3.9 1834 5 86.5 4.6 11.8 140 3.4 3.7 1732 6 87.3 4.3 11.3 158 3.3 3.5 1681
[0104] The mechanical properties of the steel in this embodiment of the invention were tested according to GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature" and GB / T 229-2020 "Metallic materials, Charpy impact test method". The elastic modulus was calculated using the method specified in GB / T 228.1-2021 or ASTM E111-17, by the slope of the initial linear segment of the stress-strain curve, and the result was taken as the average value of three parallel specimens.
[0105] In this embodiment of the invention, the corrosion resistance test of steel was conducted using a laboratory periodic immersion corrosion test and an accelerated corrosion test to simulate a seawater splash environment. An accelerated corrosion test was performed on the embodiment of the invention, and a 40mm thick DH36 steel plate was used as a comparative example. The test solution was a 3.5% neutral NaCl solution. The ambient temperature was 40±2℃, the solution temperature was 35±2℃, and the humidity was 60±5%RH. The sample rotation speed was 3r / h. Other conditions were performed according to GB / T 19746 "Corrosion of Metals and Alloys - Periodic Immersion Tests in Salt Solutions". Each wet-dry cycle lasted 60min (10min immersion, 50min drying), and the periodic immersion corrosion cycles were 168h and 360h, respectively. The average corrosion rate (g / m³) was calculated using the weight loss method. 2 •h) Evaluate the corrosion resistance of the steel plate.
[0106] In this embodiment of the invention, the microstructure of steel was detected using an optical microscope and a scanning electron microscope (SEM). The ferrite volume fraction and grain size were determined according to GB / T 6394-2017. The volume fraction, average size, and distribution density of TiB2 reinforcing phase particles were obtained through quantitative analysis of SEM images. At least 10 fields of view were randomly selected at magnification of 5000–10000x, with each field having a statistical area ≥1000 μm². The results were averaged, and the measurement error was controlled within ±10%. The average spacing of pearlite lamellae was determined using the SEM scale calibration and vertical lamellar line intercept method described above. At least 50 effective spacing data were collected for each embodiment, and the arithmetic mean was taken.
[0107] The offshore wind power steel plate produced using this invention has a ferrite + bainite + pearlite multiphase microstructure, wherein the ferrite volume fraction is 80%~90%, the average grain size is grade 9~10, the pearlite lamellar spacing is ≤200nm, and TiB2 hard reinforcing particles with a volume fraction greater than 3% are dispersedly distributed, with an average particle size <5μm and a distribution density of 1500~2500 particles / mm². The steel plate of this invention has an elastic modulus ≥220GPa, yield strength ≥360MPa, tensile strength 490~630MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and an average corrosion rate (g / m³) of 168h under 3.5% neutral NaCl solution conditions. 2 The average corrosion rate (g / m³) over a corrosion cycle of 360 hours is 0.75~0.79. 2 With a modulus of 0.70~0.75, it combines high elastic modulus, good ductility, low-temperature toughness and resistance to seawater splash corrosion, making it suitable for structures such as the lower section of offshore wind turbine towers and the upper part of jackets, and can meet the requirements for long-term safe service in seawater splash environments.
[0108] To illustrate the present invention, the present invention has been appropriately and sufficiently described above through embodiments. The above embodiments are only for illustrating the present invention and are not intended to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Any modifications, equivalent substitutions, improvements, etc., should be included within the protection scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A 36kg-grade offshore wind power steel with high elastic modulus, characterized in that, The elemental composition of the wind power steel, by mass percentage, is as follows: C: 0.035%~0.045%, Si: 0.15%~0.25%, Mn: 0.80%~0.90%, Cr: 1.5%~2.5%, Cu: 0.25%~0.40%, Nb: 0.02%~0.03%, Ti: 1.5%~2.5%, B: 0.6%~1.2%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, and -0.6%≤Ti-2.22×B≤0.6%, Cr / Cu: 3.75~10.00; the remainder is Fe and unavoidable impurities.
2. The 36kg-grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The microstructure of the wind power steel includes ferrite, bainite and pearlite, with TiB2 hard reinforcing particles dispersed throughout the steel.
3. The 36kg-grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The ferrite volume percentage is 80%~90%, the average ferrite grain diameter is 11~16μm; the pearlite lamellar spacing is ≤200nm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction of ≥3%, an average particle size of <5μm, and a distribution density of 1500~2500 particles / mm².
4. The 36kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The steel plate for wind power has an elastic modulus ≥220GPa, yield strength ≥360MPa, tensile strength 490~630MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and a plate thickness of 20~60mm.
5. A method for producing 36kg-grade offshore wind power steel with high elastic modulus as described in any one of claims 1-4, characterized in that, This includes smelting, continuous casting, heating, controlled rolling, and controlled cooling; Heating: The continuous casting billet is heated at 1100~1150℃ for a total duration of 4~5 hours; Controlled rolling: A three-stage controlled rolling process is adopted after the continuous casting billet is heated; The first stage of rolling starts at a temperature of 980~1050℃ and has a cumulative reduction rate of ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%. The second-stage rolling temperature is 860~890℃, and the average single-pass reduction rate is ≥20%. The third stage of rolling begins at a rolling temperature of 780~800℃, with a cumulative reduction rate of 18%~24%, and is rolled to the target thickness. Controlled cooling: After straightening, the steel plate is initially cooled at 730~750℃ and then enters a rapid laminar flow cooling system at a cooling rate of 5~8℃ / s, with a reddening temperature of 560~600℃. After cooling, the steel plate is subjected to slow cooling for ≥24 hours.
6. The method for producing 36kg-grade offshore wind power steel with high elastic modulus according to claim 5, characterized in that, Smelting includes converter or electric furnace smelting, LF refining, and RH refining; During the LF refining stage, P ≤ 0.01% and S ≤ 0.002% are controlled, and before the RH refining is completed, the total oxygen in the molten steel is controlled to ≤ 20 ppm. Ti and B elements are added during the LF refining and alloying stage, and the argon blowing time during the refining process is ≥40min. RH refining time ≥30min, tapping superheat ≤25℃.
7. The method for producing 36kg-grade offshore wind power steel with high elastic modulus according to claim 5, characterized in that, The continuous casting process also includes electromagnetic stirring technology. The electromagnetic stirring current in the continuous casting crystallizer is 550~600A and the frequency is 5~7Hz. The second cooling section adopts electromagnetic stirring at the solidification end, with an F-EMS current of 460~520A and a frequency of 3~5Hz.
8. The method for producing 36kg-grade offshore wind power steel with high elastic modulus according to claim 5, characterized in that, The secondary cooling section adopts a zoned cooling method, with the specific water content in the foot roller section, bending section, and straightening section controlled at 0.28~0.34L / kg, 0.20~0.27L / kg, and 0.12~0.17L / kg, respectively; the billet is slowly cooled after exiting the machine.
Citation Information
Patent Citations
Normalized condition 36kg-level maritime work steel plate and production method thereof
CN106148833A
A method for preparing 80-100mm thick EH36 steel for offshore wind power
CN111455255B
Large-piece-weight extra-thick steel for offshore wind power and production method thereof
CN111676424A
Marine wind power steel with high fracture toughness and low aging sensitivity and production method thereof
CN111809117A
Low-carbon-equivalent extra-thick offshore wind power steel DH36 steel plate and production method thereof
CN112176248A